Neurological Short-Term Outcomes of a Cohort of Children Born to Zika Virus-Infected Mothers in Barcelona - Natàlia Romaní; Maria Pieras; Marie Antoinette Frick; Elena Sulleiro; Carlota Rodó; Aroa Silgado; Anna Suy; Maria Espiau; Claire Thorne; Carlo Giaquinto; Ana Felipe-Rucián; Pere Soler-Palacín; et al. (MDPI AG, 2022)
Zika virus (ZIKV) is a vector-borne flavivirus with a known teratogenic effect, yet the full spectrum has not been delineated. Studies on endemic areas tried to characterize the clinical outcomes of ZIKV intrauterine exposure. We aimed to describe early neurodevelopmental outcomes on prenatally ZIKV-exposed children in a non-endemic ZIKV area. This is a prospective observational cohort study conducted from May 2016 to December 2021 at Hospital Universitari Vall d'Hebron in Barcelona, Catalonia, Spain. We monitored for up to 24 months 152 children extracted from a pregnant women cohort with suspected ZIKV infection; eleven women (11/150; 7.3%) fulfilled the criteria for a confirmed ZIKV infection. Among the 152 children included, we describe two cases of congenital ZIKV syndrome (CZS) born from women with a confirmed ZIKV infection. Additionally, we describe five cases of other potentially ZIKV-related outcomes (OPZROs), all with normal birth cranial circumference and born to women with probable ZIKV infection. The low exposed prevalence of adverse outcomes in asymptomatic children at birth in a non-endemic area suggests that close follow-up should be addressed by primary care pediatricians instead of pediatric specialists. Further studies are needed to assess the effects of ZIKV intrauterine exposure beyond two years of life.